Marketing Strategy For Grenzelos - Nugraha, Adhitya; Larso, Dwi (The Indonesian Journal of Business Administration, 2015)
Abstract.Fitness industry in Indonesia is growing and becoming urban lifestyle, but there has not been a clothing designated for fitness activity. Grenzelos, engaged in fashion field, tries to capture this opportunity by offering premium-classed fitness wear products. However, as the new company Grenzelos perform operations using only owner intuition, so it cannot reach the market. This causes Grenzelos need to consider the marketing strategy to be done.Based on the external analysis, the external analysis shows the attractiveness of this new industry with its high demand. Internal analysis shows that the consumer segment for fitness clothing is a body builder. Additionally, Grenzelos has done test marketing in the form of beta testing done in two phases to determine the customers' response and demand levels. In a SWOT analysis found that Greenzelos fitness clothing is a superior product in terms of quality and design, but there is no clear standard price with a limited distribution. In addition, people's lifestyles that lead to a healthy life and good appearance, and the use of technology for shopping activity may be an opportunity that can be exploited by Grenzelos, while the capital strength of the nearest competitor and limited market can be a threat. This led the company still does not have a clear presence in the fitness apparel market that is prone to competitor products.IFAS - EFAS continued SWOT, 3.30 point for IFAS and 2.90 point. From IFAS-EFAS results, it can be seen that Grenzelos is in diversification quadrant. So, it needs a marketing strategy that can reach the market. So, Grenzelos need a marketing strategy that can reach the market. This marketing strategy using marketing mix that starts from the development of product design, sales made through cooperation with existing online stores, lower prices than major competitors and promotion system using the IMC (Integrated Marketing Communication) method.To implement the new strategy for Grenzelos, this final project generate the plan and budgeting for the company. These implementation plan and budgeting covers the proposed marketing mix activities for the period of one year with total cost of Rp 159 million.Keywords: Fitness, Beta Testing, Grenzelos, Marketing Strategy